1980
DOI: 10.1128/jcm.11.1.19-21.1980
|View full text |Cite
|
Sign up to set email alerts
|

Liquid medium for growth of Legionella pneumophila

Abstract: The medium described is a simple yeast extract broth capable of growing large number of Legionella neumophila, the causative organism of Legionnaires disease. Filtration was chosen as a means of sterilization, since medium that was autoclaved did not support growth without the presence of Norite A. The filtered medium gave rapid cell growth and maintained the initial antigen production. The observed generation time was 99 min with a maximum cell population of 2 X 10(2) COLONY-FORMING UNITS PER ML IN APPROXIMAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(53 citation statements)
references
References 5 publications
1
50
2
Order By: Relevance
“…). As mentioned above, L. pneumophila exhibits a putative serine transport protein (Lpp2269) to take up serine from the medium , and serine is an important carbon and energy source for L. pneumophila during growth in medium . It was also mentioned that cell‐free extracts of L. pneumophila exhibit high serine dehydratase activity .…”
Section: Metabolic Features Of L Pneumophila In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…). As mentioned above, L. pneumophila exhibits a putative serine transport protein (Lpp2269) to take up serine from the medium , and serine is an important carbon and energy source for L. pneumophila during growth in medium . It was also mentioned that cell‐free extracts of L. pneumophila exhibit high serine dehydratase activity .…”
Section: Metabolic Features Of L Pneumophila In Vitromentioning
confidence: 99%
“…Early (radiotracer) experiments revealed that amino acids serve as the main carbon and energy source of L. pneumophila when growing in vitro in different media . From these experiments, Ser, Thr, Glu and Tyr were identified as preferred substrates in vitro , and Cys, Gln, Ser, Met, Val, Glu, Tyr, Thr and Arg were shown to support growth in vivo .…”
Section: Metabolic Features Of L Pneumophila In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…pUC18 [8] was used as a vector for plasmid construction and pGEM-T (Promega) as a PCR product cloning vector. E. coli was grown on/in LB medium at 37³C with or without 1.5% agar [9] and L. pneumophila was grown in BCYE agar (Difco) plates or YEB [10] at 35³C.…”
Section: Bacterial Strains Plasmid and Growth Conditionsmentioning
confidence: 99%
“…Growth and radiolabeling. Kinetics of growth were determined by inoculating organisms into 20 ml of yeast extract broth (YEB [26]; 10 g of yeast extract, 0.4 g of L-cysteine hydrochloride, 0.25 g of ferric pyrophosphate [pH 6.9]) and the optical density at 660 nm (OD6w) was monitored at hourly intervals. To minimize accumulation of superoxide radicals, which are reported to have a toxic effect oh growing cells (15), the following steps were taken: (i) culture medium was sterilized by filtration through a 0.2-,um Millipore filter instead of by autoclaving, (ii) cysteine was added just before inoculation, and (iii) the media were protected from light during bacterial growth.…”
mentioning
confidence: 99%